Progression in immunotherapy for advanced prostate cancer - Liang, Hao; Liu, Yang; Guo, Jiao; Dou, Maoyang; Zhang, Xiaoyi; Hu, Liyong; Chen, Jun (Frontiers in Oncology, 2023)
Prostate cancer is one of the most common malignant cancers of the male genitourinary system and has high morbidity and mortality. Currently, treatment modalities for localized prostate cancer focus mainly on radical prostatectomy or radical radiation therapy. Some patients still experience disease recurrence or progression after these treatments, while others are already at an advanced stage or have metastases at the time of diagnosis. With the continuous development and progress of medicine in recent years, immunotherapy has become a revolutionary cancer treatment, and has achieved remarkable accomplishments in the treatment of hematologic malignancies. A variety of immunotherapies have also appeared in the field of advanced prostate cancer treatment, including therapeutic vaccines and immune checkpoint therapies. Despite the discrepancy between the results of some immunotherapy studies, immunotherapy for prostate cancer has shown some initial success, especially in combination immunotherapies. Currently, immunotherapy is mainly used in advanced prostate cancer, especially in patients with metastatic castration-resistant prostate cancer. However, with the development of more clinical trials of immunotherapy, more evidence will be provided supporting the rational application of immunotherapy in the future.